2008
DOI: 10.1128/mcb.01359-07
|View full text |Cite
|
Sign up to set email alerts
|

CARD6 Is Interferon Inducible but Not Involved in Nucleotide-Binding Oligomerization Domain Protein Signaling Leading to NF-κB Activation

Abstract: We have previously reported the cloning and characterization of CARD6, a caspase recruitment domain (CARD)-containing protein that is structurally related to the interferon (IFN)-inducible GTPases. CARD6 associates with microtubules and with receptor-interacting protein 2 (RIP2). RIP2 mediates NF-B activation induced by the intracellular nucleotide-binding oligomerization domain (NOD) receptors that sense bacterial peptidoglycan. Here we report that the expression of CARD6 and RIP2 in bone marrow-derived macro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 39 publications
(57 reference statements)
0
28
0
Order By: Relevance
“…6 Notably, CARD6 is expressed ubiquitously in various tissues including the heart, 5 but it is unclear whether its expression levels are altered under pathological stimulus. In the present study, we found that in response to hypertrophic stress, CARD6 expression was increased progressively in adaptive hypertrophy (the first 2 and 4 weeks after hypertrophy stimuli) and then markedly decreased in maladaptive cardiac remodeling (the past 4 weeks).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…6 Notably, CARD6 is expressed ubiquitously in various tissues including the heart, 5 but it is unclear whether its expression levels are altered under pathological stimulus. In the present study, we found that in response to hypertrophic stress, CARD6 expression was increased progressively in adaptive hypertrophy (the first 2 and 4 weeks after hypertrophy stimuli) and then markedly decreased in maladaptive cardiac remodeling (the past 4 weeks).…”
Section: Discussionmentioning
confidence: 99%
“…A detailed Methods section is available in the online-only Data Supplement, which includes detailed methods on the following: Reagents, Human Heart Samples, Animal Models and Procedures, 6 Echocardiography Evaluation, 13,14 Histological Analysis, Quantitative Real-Time Polymerase Chain Reaction (PCR) and Western Blotting, Cultured Neonatal Rat Cardiomyocytes (NRCMs) and Recombinant Adenoviral Vectors, [14][15][16] and Statistical Analysis.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The growth of primary MEFs in culture was analyzed as previously described (35). Purified B cells were treated with 1 μg/mL LPS for 24 h. Purified T cells were stimulated by seeding on plates precoated with anti-CD3 and anti-CD28 antibodies as previously described (45). Statistical differences in cell growth were assessed using Student's t test.…”
Section: Methodsmentioning
confidence: 99%